An ab-initio study to investigate the structural, mechanical, electrical, optical and thermal properties of the AZrO3 (A= Mg, Ca, Sr, Ba, Sn, Cu) compounds. (March 2023) - Atikur Rahman, Md.; Hasan, Wakil; Khatun, Rukaia; Zahid Hasan, Md.; Hafijur Rahman, Md.; Sarker, Sushmita; Hasan, Mahbub; Lubna, Jannatul Ferdous
Abstract: Density Functional Theory (DFT) based ab -initio manner has been executed for investigating the comparative study of lead-free cubic-type perovskites materials AZrO3 (A= Mg, Ca, Sr, Ba, Sn, Cu). This is the first comparative theoretical investigation of these materials, which is done through Cambridge Serial Total Energy Package module. Extremely good relation has been observed between the synthesized structural and calculated structural values of all the compounds. Mechanical structural stability of all the phases has been confirmed from the investigated elastic stiffness parameters. The comparative elastic moduli show good agreement with previously investigated data. Ductile nature of MgZrO3, CaZrO3, SnZrO3, CuZrO3 and brittle nature of SrZrO3, and BaZrO3 have been observed from analyzing of polycrystalline elastic moduli. High Young's modulus and hence the hardness of BaZrO3 among the studied compounds ensured that this phase has more ability to resist longitudinal stress and has industrial applications. Very small Young's of CuZrO3 ensured the application of it as thermal barrier coating (TBC) material. Semiconducting nature of compounds MgZrO3, CaZrO3, SrZrO3, BaZrO3, SnZrO3 and metallic nature of CuZrO3 has been ensured after analyzing of electronic and optical features. Prominent absorption and conductivity is observed at UV energy region where CaZrO3, SrZrO3 have exceptional absorption and conductivity than others. High reflectivity in the high energy site ensured the useful applications of all these phases as good solar reflector in UV region. Thermodynamic features of AZrO3 (A= Mg, Ca, Sr, Ba, Sn, Cu) have been calculated and discussed in details for the first time. Very low thermal conductivity of these phases insured that they may be used as thermal barrier coating materials (TBC). Graphical Abstract: Detail comparative study of the physical phenomena of lead-free cubic-type perovskites materials AZrO3 (A= Mg, Ca, Sr, Ba, Sn, Cu) has been carried out through density functional theory simulation depend on CASTEP code. Very good relation has been observed between the synthesized and calculated structural values of all the compounds. Stability of these phases has been ensured from the elastic stiffness parameters. Fig. 1: Crystal structure of perovskites AZrO3 (A= Mg, Ca, Sr, Ba, Sn, Cu). Fig. 2: Mechanical features of perovskites AZrO3 (A= Mg, Ca, Sr, Ba, Sn, Cu). Ductile character of MgZrO3, CaZrO3, SnZrO3, CuZrO3 and brittle character of SrZrO3, and BaZrO3 have been observed from analyzing of polycrystalline elastic moduli. High Young's modulus and hence the hardness of BaZrO3 among the studied compounds ensured that this phase has more ability to resist longitudinal stress and has industrial applications. Very small Young's of CuZrO3 ensured the application of it as thermal barrier coating (TBC) material. Semiconducting behavior of phases MgZrO3, CaZrO3, SrZrO3, BaZrO3, SnZrO3 and metallic behavior of CuZrO3 has been ensured after analyzing of electronic and optical features. High reflectivity in the high energy site ensured the useful applications of all these phases as good solar reflector in UV region. The Debye temperatures of all the phases have been calculated utilizing the elastic constants. ga1